Kitakyushu Model Subsector : Interplay between Solid Waste and Urban Flood Risk - World Bank Group (World Bank, Tokyo, 2018)
The Kitakyushu Model is a methodology developed in Kitakyushu City, Japan to provide appropriate solutions for environmental challenges to pursue sustainable urban development. It strives to be a methodology that allows cities to easily apply sustainability more broadly and in a holistic fashion, beyond isolated projects and individual advice. The objective of this piece is to enhance the current Kitakyushu Model by adding a subsector on the linkage between solid waste management and disaster risk management, particularly flood events.